2021
DOI: 10.1016/j.cmi.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, virologic and immunologic features of a mild case of SARS-CoV-2 reinfection

Abstract: Objectives We report a case of SARS-CoV-2 reinfection 6 months after the first infection in a young healthy female physician. Both episodes led to mild COVID-19. Methods SARS-CoV-2 infections was detected by RT-PCR on naso-pharyngeal specimens. Reinfection was confirmed by whole-genome sequencing. Kinetics of total anti-S receptor binding domain immunoglobulins (Ig anti-S RBD), anti-nucleoprotein (anti-N) and neutralizing antibodies were determined in serial serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Previous studies showed that virus-specific memory CD8+ T-cells were found to persist for up to 6 years after a SARS associated coronavirus infection, but memory B-cells and accompanying antibodies were undetectable at that time [172]. However Vetter et al hypothesized that reinfection can be due to a loss of protection elicited after the first episode for a progressive reduction of protective antibody titers [144,173].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that virus-specific memory CD8+ T-cells were found to persist for up to 6 years after a SARS associated coronavirus infection, but memory B-cells and accompanying antibodies were undetectable at that time [172]. However Vetter et al hypothesized that reinfection can be due to a loss of protection elicited after the first episode for a progressive reduction of protective antibody titers [144,173].…”
Section: Discussionmentioning
confidence: 99%
“…We note that the simulations in this work are based on the epidemic curve in Geneva, Switzerland, and that seroprevalence estimation bias caused by decaying sensitivity will depend on the timing of serosurveillance with respect to the number and amplitude of preceding epidemic waves, with larger and more distal waves being more severely under-estimated. Even for mild infections, which are thought to elicit less robust immune responses ( 24 ), the sensitivity of anti-RBD and anti-N total Ig Roche tests remained close to 100% after more than 8 months post-infection. These results suggest that both Roche immunoassays are suitable for seroprevalence estimation at longer times post-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-two studies were determined to be of good quality while nine studies were of fair quality (S3 Table). Studies were primarily downgraded for unclear study objectives[63], incomplete case definition[16, 28, 48, 66, 67, 70, 77, 83], non-consecutive subject recruitment[19, 27, 30, 34, 38, 39, 4446, 49, 71, 79, 80, 86, 90], incomparable subjects[79], inadequate length of follow-up[43, 63], inadequate description of statistical methods[39, 46, 80] and inadequate description of results[39, 78]. The most common cause for downgrading studies was non-consecutive recruitment which raised concerns that the included sample could be biased towards a more severe presentation or included more individuals undergoing routine screening.…”
Section: Resultsmentioning
confidence: 99%